The independent domination number of random graph - Wang, Changping (Utilitas Mathematica, 2010)
In this note, we study the independent domination number in the random graph G(n, p). We show that asymptotically almost surely the independent domination number i(G) achieves a finite number of values for G ∈ G(n, p).